Handbook of research on comparative human resource management - Brewster, Chris (Edward Elgar Publishing Ltd. CheltenhamGB, 2012)
Examines some of the theoretical and conceptual issues, and some of the research problems that arise in comparative HRM. Takes a critical look at HRM and comparative HRM. Examines tasks and themes in comparative HRM, viz recruitment and selection, pay and rewards, training and development, management development, employment relations, human resources department, employees' contracts, careers, flexible working practices, financial participation, performance management, diversity and e-HRM.